DOI: 10.33915/etd.2642
|View full text |Cite
|
Sign up to set email alerts
|

Linear engine development for series hybrid electric vehicles

Abstract: Linear Engine Development for Series Hybrid Electric Vehicles by Csaba Tóth-Nagy This dissertation argues that diminishing oil reserves, concern over global climate change, and desire to improve ambient air quality all demand the development of environment-friendly personal transportation. In certain applications, series hybrid electric vehicles offer an attractive solution to reducing fuel consumption and emissions. Furthermore, linear engines are emerging as a powerplant suited to series HEV applications. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 45 publications
(80 reference statements)
1
10
0
Order By: Relevance
“…Furthermore, the OLEA operates only on a few moving parts, that is, translator rod and mechanical springs. The elimination of crankshaft linkages in the design allows unrestricted piston motion, thereby exhibiting different stroke and variable compression ratio every cycle [4,5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the OLEA operates only on a few moving parts, that is, translator rod and mechanical springs. The elimination of crankshaft linkages in the design allows unrestricted piston motion, thereby exhibiting different stroke and variable compression ratio every cycle [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the short residence of the piston at the Top Dead Center (TDC) and a faster expansion stroke are beneficial for reducing heat transfer losses, thereby improving the thermal efficiency [7] (v) Minimal vibration: elimination of crankshaft mechanical linkages reduces the associated forces and moments in the OLEA system, thereby cutting back the vibrations in the OLEA system when compared to crankshaft engine. However, of all the OLEA configurations, the opposed piston configuration with equal piston masses enjoys the benefits of minimal vibrations, whereas single cylinder OLEA is more prone to the vibrations [5,7]. The vibrations of the dual cylinder configuration lie in between the single cylinder and opposed piston configuration.…”
Section: Introductionmentioning
confidence: 99%
“…This fed the development of a second generation diesel fueled prototype. In this, a boosted, direct injected, port scavenged, dual cylinder engine operated between 50 and 60 Hz [19]. These research efforts revealed many important insights into the operation of the linear engine.…”
Section: Free Piston Linear Enginesmentioning
confidence: 99%
“…Researchers from WVU correlated the model constant ( ) with experimental data gathered from a free piston linear engine and validated the model in ring-down testing [19], showing good success for the model. The same research suggested that the damping coefficient should be dependent on the piston bore and translator mass.…”
Section: Eq 39mentioning
confidence: 99%
“…The prototype represented a diesel fueled, boosted, direct injected, port scavenged and dual cylinder engine. It was operating within a frequency range of 50 to 60 Hz [25]. Another prototype was built in 2007 by Newcastle University.…”
Section: Review Of Literaturementioning
confidence: 99%